A Bright Spatially-Coherent Compact X-ray Synchrotron Source - Kneip,S; McGuffey,C; Martins,JL; Martins,SF; Bellei,C; Chvykov,V; Dollar,F; Fonseca,R; Huntington,C; Kalintchenko,G; Maksimchuk,A; Mangles,SPD; et al. (Nature Physics, 2009)
Each successive generation of x-ray machines has opened up new frontiers inscience, such as the first radiographs and the determination of the structureof DNA. State-of-the-art x-ray sources can now produce coherent high brightnesskeV x-rays and promise a new revolution in imaging complex systems on nanometreand femtosecond scales. Despite the demand, only a few dedicated synchrotronfacilities exist worldwide, partially due the size and cost of conventional(accelerator) technology. Here we demonstrate the use of a recently developedcompact laser-plasma accelerator to produce a well-collimated,spatially-coherent, intrinsically ultrafast source of hard x-rays. This methodreduces the size of the synchrotron source from the tens of metres tocentimetre scale, accelerating and wiggling a high electron chargesimultaneously. This leads to a narrow-energy spread electron beam and x-raysource that is >1000 times brighter than previously reported plasma wiggler andthus has the potential to facilitate a myriad of uses across the whole spectrumof light-source applications.